Entrepreneurship in Finance Successfully Launching and Managing a Hedge Fund in Asia - Arslanian, Henri (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
Thinking of launching your own hedge fund? Want to learn more about the different steps involved in setting-up your own hedge fund in Asia? Want to raise capital from institutional investors? This book is the first hands-on publication to set out the various steps and considerations necessary to successfully launch and manage a hedge fund in Asia in concrete and practical terms. It is written for: · any individual or team aiming to launch a hedge fund in Asia and seeking practical and experienced guidance; · any existing hedge fund manager requiring advice on global best practices in order to grow and attract institutional-quality capital and investors; · any fund manager or other industry participant globally intending to set up a presence in Asia or simply wishing to find out more about the hedge fund industry in Asia; · any academic looking to learn more about the practical aspects of the hedge fund industry to complement his or her academic research; · any student hoping to discover more about the hedge fund industry as a career choice. This book covers the essential elements that a talented entrepreneur in finance needs to consider in order to launch his or her own hedge fund in Hong Kong or Singapore. It places particular focus on the legal, regulatory, fund structuring, tax, governance, capital raising, talent, office space, technology, operational and budgeting considerations, from the pre-launch phase to the expansion and institutionalisation of the business. Whilst most other hedge fund books cover the investment side of the hedge fund business (e.g., different hedge fund strategies, asset class selection, portfolio modelling/construction, portfolio risk management), this book specifically provides in-depth insights into the crucial - and often misunderstood - non-investment aspects involved in launching a hedge fund business. In addition, whilst this book focuses mainly on the hedge fund industry, most sections of the book are equally applicable to anyone launching a family office or any type of traditional (e.g., long only) or alternative asset management firm (e.g., private equity, venture capital).